Jahresbericht 1987 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1988)
Fischer, Alexander ; Rütimann, Christoph ; Plowden, David ; Golub, Leon ; Schmalix, Hubert ; Giacometti, Augusto ; Le Corbusier ; Cragg, Tony ; Schärer, Hans ; Thomkins, André ; etc.
Duits
boek